Evaluación del rendimiento del proceso de poliéster y algodón (PES /CO) de la Empresa Insomet, ubicada en la parroquia Pastocalle Latacunga. - Cevallos Soria, Milton Ruben (2018)
In this research, a polyester and cotton processes called intimate mixture performance evaluation was carried out, which aim is to minimize the garbage waste, flat and Wype in the cardado lines, manuares and open end, for which, a survey of the processes allowed to understand the sequence and type of process, in the case of Insomet is continuous since their lines do not comply with stoppages to supply themselves and their cycle times depend on the machines speed, another activity is the product monitoring and people understanding that the follow-up to the operators in the production lines where the cause or the bottleneck system was found, that a once identified, it was analyzed by means of control diagrams and determining the impact it has on the mechanical components and the raw material, to quantify these variables we used a technique: the mass balance, but very useful if variables such as consumption and energy are eliminated since in the production of lint there is no chemical reaction but if readjusting consistently to deformation whose resulting equation uses variables such as inputs and outputs this in turn transforming them into monetary values, shows the losses that it is held at the system borders, for which, a reuse method implementation was proposed, which was subjected to a capacity process study to minimize polyester and cotton material losses.